New Research Advances on Marine Invertebrates - Alexandre Lobo-da-Cunha (Journal of Marine Science and Engineering, 2022)
Marine ecosystems encompass a wide variety of invertebrates, pelagic and benthonic, from intertidal to deep-sea habitats in polar to tropical regions [...]